Emerging Role of Exosomes in Retinal Diseases - Zhang, Zhengyu; Mugisha, Aime; Fransisca, Silvia; Liu, Qinghuai; Xie, Ping; Hu, Zizhong (Frontiers in Cell and Developmental Biology, 2021)
Retinal diseases, the leading causes of vison loss and blindness, are associated with complicated pathogeneses such as angiogenesis, inflammation, immune regulation, fibrous proliferation, and neurodegeneration. The retina is a complex tissue, where the various resident cell types communicate between themselves and with cells from the blood and immune systems. Exosomes, which are bilayer membrane vesicles with diameters of 30-150 nm, carry a variety of proteins, lipids, and nucleic acids, and participate in cell-to-cell communication. Recently, the roles of exosomes in pathophysiological process and their therapeutic potential have been emerging. Here, we critically review the roles of exosomes as possible intracellular mediators and discuss the possibility of using exosomes as therapeutic agents in retinal diseases.